Synthesis and Electrochemical Study of 1,1′-Thienyl-Substituted Fused Bis-germatranes with a Core 5c-6e Hyperbond - Romanovs, Vitalijs; Spura, Jana; Jouikov, Viatcheslav (Synthesis, 2018)
Novel fused bis-germatranes containing three hypercoordinated atoms (two Ge and one N) and substituted at the 1,1′-positions with bromo-thienyl groups [(3-bromo-2-thienyl)-, (3,5-dibromo-2-thienyl)-, and 3-(4-bromo)-2-thienyl] have been synthesized from the corresponding triethoxy(thienyl)germanes and tris(1,3-dihydroxypropan-2-yl)amine. The doubly degenerated HOMO and HOMO-1 in these compounds are localized on the thienyl substituents while a 5c-6e hyperbond of the bis-germatranyl core (C–Ge←N→Ge–C system) is only a lower lying HOMO-2. Square-wave pulse voltammetry in CH3CN/0.1 M Bu4NPF6 shows all three compounds to undergo reversible electrochemical oxidation affecting one thienyl substituent. The DFT B3LYP/Lanl2DZ//HF/6-311G(d,p) calculations of their cation radicals suggest the enhancement and shortening of the N→Ge intramolecular dative bond on the side of the oxidized thienyl unit because of the positive charge and the increased acceptor character of the latter; this is accompanied by the loss of the N→Ge dative bond on the side of the non-oxidized substituent and a substantial pyramidalization of the Ge atom.
Keywords: bis-germatranes; cation radicals; hyperbonds; electrochemical oxidation